CARE 2013 explanations and elaborations: Reporting guidelines for case reports - Riley, D; Barber, M; Kienle, G; Aronson, J; von Schoen-Angerer, T; Tugwell, P; Kiene, H; Helfand, M; Altman, D; Sox, H; Werthmann, P; Moher, D; et al. (Elsevier, 2017)
Well-written and transparent case reports (1) reveal early signals of potential benefits, harms, and information on the use of resources; (2) provide information for clinical research and feedback on clinical practice guidelines (CPGs), and (3) inform medical education. High-quality case reports are more likely when authors follow reporting guidelines. During 2011-2012 a group of clinicians, researchers, and journal editors developed recommendations for the accurate reporting of information in case reports that resulted in the CARE (CAse REport) Statement and Checklist. They were presented at the 2013 International Congress on Peer Review and Biomedical Publication, have been endorsed by multiple medical journals, and translated into nine languages. This explanation and elaboration document has the objective to increase the use and dissemination of the CARE Checklist in writing and publishing case reports. Each item from the CARE Checklist is explained and accompanied by published examples. The explanations and examples in this document are designed to support the writing of high-quality case reports by authors and their critical appraisal by editors, peer reviewers, and readers. This article and the 2013 CARE Statement and Checklist, available from the CARE website [www.carestatement. org] and the EQUATOR Network, [www.equator-network.org] are resources for improving the completeness and transparency of case reports.